Higher endogenous nitrite levels are associated with superior exercise capacity in highly trained athletes - Totzeck, M.; Hendgen-Cotta, U. B.; Rammos, C.; Frommke, L.-M.; Knackstedt, C.; Predel, H.-G.; Kelm, M.; Rassaf, T. (Nitric Oxide, 2015)
Factors improving exercise capacity in highly trained individuals are of major interest. Recent studies suggest that the dietary intake of inorganic nitrate may enhance athletic performance. This has been related to the stepwise in vivo bioactivation of nitrate to nitrite and nitric oxide (NO) with the modulation of mitochondrial function. Here we show that higher baseline levels of nitrite are associated with a superior exercise capacity in highly trained athletes independent of endothelial function. Eleven male athletes were enrolled in this investigation and each participant reported twice to the testing facility (total of n = 22 observations). Venous blood was obtained to determine the levels of circulating plasma nitrite and nitrate. Endothelial function was assessed by measuring flow-mediated vasodilation (FMD). Hereafter, participants completed a stepwise bicycle exercise test until exhaustion. Blood was drawn from the ear lope to determine the levels of lactate. Lactate anaerobic thresholds (LAT) in relation to heart rate were calculated using non-linear regression models. Baseline plasma nitrite levels correlated with LATs (r = 0.65; p = 0.001, n = 22) and with endothelial function as assessed by FMD (r = 0.71; p = 0.0002). Correlation coefficients from both testing days did not differ. Multiple linear regressions showed that baseline plasma nitrite level but not endothelial function was an independent predictor of exercise capacity. No such correlations were determined for plasma nitrate levels.